(untitled) (Brazilian Journal of Radiation Sciences, 2021)
The Very High Temperature Reactor (VHTR) is one of the candidates of next generation of the nuclear reactors according to IAEA. Predicting the thermohydraulic behavior of High Temperature Reactors (HTR) is an important contribution to the development of this technology. Evaluation of thermohydraulic performance and a comparison with experimental data were proposed to the international research community. The impact of porosity of pebble beds in the thermohydraulic performance in normal operation and under accident condition is the goal of many kinds of research. In this sense, the three-dimensional CFD thermohydraulic simulation of a HTR using ANSYS CFX has been done. The full-scale approach is used to study the influence of different porosity scheme in the main structural materials of the HTR-10 reactor. The porous medium model was used to simulate the pebble bed core zone and the discharge system of pebbles. A comparison with experimental data was made. The steady-state thermohydraulic performance of the HTR-10 reactor at normal operation and anticipated transients without scram (ATWS) tests result, were used. In this work, was possible to estimate the effect of the porosity in the interior regions of the reactor and the impact on the temperature distribution. Finally, the study broadens the knowledge about the impact that the use of variable porosity has on safety analyses in pebble beds reactors.